Transatlantic encounters in history of education translations and trajectories from a German-American perspective - Isensee, Fanny 1988-; Oberdorf, Andreas 1988-; Töpper, Daniel 1987- (Routledge studies in cultural history, 2020)
"In the last twenty years, transnational perspectives have gained momentum in the field of historical-educational research. Scholars have made substantial efforts to rethink nation-based historiographies by reconstructing and reinterpreting the cross-border encounters and intertwined processes that have turned the history of education into a transnational enterprise. A closer look at specific transnational spaces furthers a better understanding of these processes. Against this backdrop, the book offers case studies focusing on transatlantic encounters with special regard to the manifold entanglements between Germany and the United States of America that represent one of the most complex, dynamic, and vivid educational spaces between the eighteenth and twentieth century. Drawing on excellent source material, each contribution examines interaction processes as the genuine transformative moment within any cross-border transfer, and investigates exchanges of concepts, institutions, and materials. Under this premise, the book draws attention to shifting trajectories in the German-American history of education that can be identified by focusing on long-lasting transnational entanglements. By offering a wide range of research approaches, the publication furthermore contributes innovative methodological thoughts to transnational histories of education that go beyond the German-American context and will interest students, emerging researchers, and experts of history of education"--